Pengaruh Mekanisme Corporate Governance Dan Kualitas Audit Terhadap Integritas Laporan Keuangan - Rhika Cahyaningtyas; Dirvi Surya Abbas (LPPM Universitas Putera Batam, 2022)
This research the effect of corporate governance mechanisms and quality audit of the integrity of financial statements. The research population is 164 manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. Based on the purposive sampling method, 26 manufacturing companies that listed on the Indonesia Stock Exchange (IDX) in 2014-2018 as a sample research and a total sample of 130. The data were selected from the company's annual report and analysed using multiple linear regression. Integrity measurement financial statements using conservatism. The results of the study show that managerial ownership and institutional ownership have a positive effect to the integrity of financial statements. Independent commissioners, audit committees, and audit quality has no effect on the integrity of the financial statements